Environmental Sanitation Education for Pregnant Women as an Effort to Prevent Stunting in Children in Lamongan - Nikmah, Khusnul; Eka Sarofah Ningsih; Lilik Darwati; Aulia Dwiyanti (Journal of Community Engagement in Health, 2025)
Stunting in children is a complex health problem with long-term impacts on physical growth, cognitive development, and future individual productivity. One contributing factor to stunting is poor environmental sanitation, particularly during pregnancy. This community service activity aims to increase the knowledge and awareness of pregnant women about the importance of environmental sanitation as a preventative measure against stunting in children. The activity was carried out in Rancangkencono Village, involving 12 pregnant women as participants. The implementation method included direct counseling, group discussions, and demonstrations of basic sanitation practices such as handwashing, using healthy latrines, and managing household waste. Evaluation was conducted by comparing pretest and posttest results to measure knowledge gains. The results showed an increase in the average knowledge score of participants from 55 in the pretest to 85 in the posttest. In addition, participants demonstrated positive changes in attitudes toward implementing clean and healthy living behaviors in the home environment. Data analysis showed that a participatory and contextual educational approach can increase the understanding and motivation of pregnant women to maintain environmental cleanliness for the health of their fetus and unborn child. Environmental sanitation education has proven to be an effective strategy in preventing stunting from pregnancy, so it needs to be implemented sustainably with cross-sector support at the community level.